Combined iron chelator and T-type calcium channel blocker exerts greater efficacy on cardioprotection than monotherapy in iron-overload thalassemic mice - Sirinart Kumfu (2018)
© 2018 Elsevier B.V. Although both iron chelators and T-type calcium channel (TTCC) blockers have been shown to exert cardioprotection by decreasing cardiac iron deposition and reducing left ventricular (LV) dysfunction via different channels in iron-overloaded rodent models, the cardioprotective effects of combined iron chelator and TTCC blocker treatment in thalassemic mice has not been investigated. We hypothesized that a combined iron chelator and TTCC blocker exerts better cardioprotection than monotherapy by decreasing cardiac iron accumulation, apoptosis and oxidative stress. An iron-overload condition was induced in heterozygous βKOthalassemic (HT) mice and wild-type (WT) mice by high iron diet consumption (FE) for 3 months. Then, the iron chelator deferiprone (DFP), the TTCC blocker efonidipine (Efo), and combined DFP plus Efo were fed via oral gavage for 1 month whilst the high iron diet was continued. LV function, heart rate variability (HRV), apoptosis and cardiac iron accumulation were determined. Chronic iron-overload in mice led to increased cardiac iron deposition, oxidative stress, apoptosis, and impaired LV function and HRV. Although DFP and Efo showed similar cardioprotective efficacy, the combined DFP plus Efo therapy exerted greater efficacy in reducing cardiac iron deposition and cellular apoptosis than either of the monotherapies in iron-overload thalassemic mice.